EuroFlow antibody panels for standardized n-dimensional flow cytometric immunophenotyping of normal, reactive and malignant leukocytes - van Dongen, J J M; Lhermitte, L; Böttcher, Sebastian; Almeida, J; van der Velden, V H J; Flores-Montero, J; Rawstron, A; Asnafi, V; Lécrevisse, Q; Lucio, P; Mejstříková, Ester; Szczepański, T; et al. (Leukemia, 2012)
Most consensus leukemia & lymphoma antibody panels consist of lists of markers based on expert opinions, but they have not been validated. Here we present the validated EuroFlow 8-color antibody panels for immunophenotyping of hematological malignancies. The single-tube screening panels and multi-tube classification panels fit into the EuroFlow diagnostic algorithm with entries defined by clinical and laboratory parameters. The panels were constructed in 2-7 sequential design-evaluation-redesign rounds, using novel Infinicyt software tools for multivariate data analysis. Two groups of markers are combined in each 8-color tube: (i) backbone markers to identify distinct cell populations in a sample, and (ii) markers for characterization of specific cell populations. In multi-tube panels, the backbone markers were optimally placed at the same fluorochrome position in every tube, to provide identical multidimensional localization of the target cell population(s). The characterization markers were positioned according to the diagnostic utility of the combined markers. Each proposed antibody combination was tested against reference databases of normal and malignant cells from healthy subjects and WHO-based disease entities, respectively. The EuroFlow studies resulted in validated and flexible 8-color antibody panels for multidimensional identification and characterization of normal and aberrant cells, optimally suited for immunophenotypic screening and classification of hematological malignancies.
Keywords: imunofenotypizace; nádorové biomarkery; Prognosis; studie případů a kontrol; Biomarkers, Tumor; Humans; Europe; monoklonální protilátky; Antibodies, Monoclonal; Leukocytes; prognóza; hematologické nádory; Flow Cytometry; Hematologic Neoplasms; Evropa; průtoková cytometrie; Immunophenotyping; lidé; Case-Control Studies; leukocyty